Deviant Women Cultural, Linguistic and Literary Approaches to Narratives of Femininity (Edition 1) - Mäntymäki, Tiina; Rodi-Risberg, Marinella; Foka, Anna (Peter Lang International Academic Publishing Group, 2014)
This multidisciplinary collection of articles illuminates the ways in which the concept of female deviance is represented, appropriated, re-inscribed and refigured in a wide range of texts across time, cultures and genres. Such a choice of variety shows that representations of deviance accommodate meaning-making spaces and possibilities for resistance in different socio-cultural and literary contexts. The construct of the deviant woman is analysed from literary, sociolinguistic and historical-cultural perspectives, revealing insights about cultures and societies. Furthermore, the studies recognise and explain the significance of the concept of deviance in relation to gender that bespeaks a contemporary cultural concern about narratives of femininity.